Hydronomic zones for developing basin water conservation strategies - Molden, David J.; Sakthivadivel, Ramaswamy; Keller, J. (International Water Management Institute, 2001)
Changes in the way water is used in one part of a river basin often affect how water is used somewhere else in that basin. This report introduces the concept of hydronomic ( hydro water + nomus management) zones that were developed to help untangle some of the complexities of basin-wide water resource use.